Tactile Feedback in Closed-Loop Control of Myoelectric Hand Grasping: Conveying Information of Multiple Sensors Simultaneously via a Single Feedback Channel - Mayer, Raphael M.; Garcia-Rosas, Ricardo; Mohammadi, Alireza; Tan, Ying; Alici, Gursel; Choong, Peter; Oetomo, Denny (Frontiers in Neuroscience, 2020)
The performance of object grasping and manipulation significantly rely on receiving the appropriate feedback information. In many cases, a combination of multiple feedback information is required simultaneously. In this paper, the efficacy of simultaneously conveying two independent sets of sensor information (grasp force and secondary information) through a single channel of feedback stimulation (vibrotactile via bone conduction) to the human user in a prosthetic application is investigated. Subject performance in two tasks: regulating the grasp force and identifying the secondary information, were evaluated when provided with either one corresponding information or both sets of feedback information. Visual feedback is involved in the training stage. The proposed approach is validated in human-subject experiments using a vibrotactile transducer worn on the elbow bony landmark (to realise a non-invasive bone conduction interface) carried out in a virtual reality environment to perform a closed-loop object grasping task. The experimental results show that the performance of the human subjects on either task, whilst perceiving two sets of sensory information, is not inferior to that when receiving only one set of corresponding sensory information.